Salvage robotic-assisted radical cystectomy is safe in patients with history of pelvic irradiation - James Kovacic; Ankur Dhar; Jonathan Kam; Andrew Shepherd; Ahmed Goolam; Matthew Winter (Current Urology)
Abstract. Objectives. To describe the surgical approach and perioperative outcomes of a multicenter series evaluating a robotic-assisted approach to radical cystectomy with total intracorporeal urinary diversion in the setting of prior pelvic radiotherapy. Materials and methods. We analyzed our prospective cystectomy database for patients who underwent robotic-assisted radical cystectomy for bladder cancer after radiotherapy between 2018 and 2022. Demographic information and data regarding preoperative factors including stage of disease, preoperative hydronephrosis, and history of pelvic radiotherapy were collected via review of electronic medical records. All operations were performed by 1 of 2 experienced urologists using the da Vinci X, Xi, or Si surgical platforms. Results. Ten patients were identified for this study. The median age of participants was 73.5 years (range, 41–84 years). The median American Society of Anesthesiologists classification score was 3 (range, 3–4). The median Charlson Comorbidity Index was 6 (range, 2–12). Among the patients, 4 out of 10 patients (40%) had muscle invasive bladder cancer before salvage surgery. Intracorporeal ileal conduit urinary diversion was performed in 8 patients, whereas 2 patients underwent intracorporeal neobladder formation. Median intraoperative blood loss was 250 mL (range, 150–600 mL), and median operative duration was 390 minutes (range, 195–450 minutes). The overall 30-day complication rate was 60% with a Clavien-Dindo grade ≥3 complication rate of 15%. Perioperative mortality was 0%. Median duration of follow-up was 210 days (range, 60–1580 days). Conclusions. This series describing the outcomes of salvage robotic-assisted radical cystectomy using total intracorporeal urinary diversion demonstrates the safety of this technique. Further studies with long-term follow-up, including oncological outcomes, are required to support the widespread adoption of this procedure.